Association between dental caries and age-specific body mass index in preschool children of an Iranian population - Ali Bagherian; Mostafa Sadeghi (Wolters Kluwer Medknow Publications, 2013)
Background: The aim of this study was to determine the association of dental caries and BMI-for-age in preschool children and whether BMI-for-age is similar or different between Severe Early Childhood Caries (S-ECC) and caries free children. Materials and Methods: Four hundred preschool children aged 30-70 months were entered into this study. The parameters examined in this study were weight, height, BMI-for-age and number of decayed, extracted and filled surfaces of deciduous teeth (defs). Based on dental caries, the subjects were also divided into S-ECC and caries-free groups. Then data was analyzed by t-test, one-way ANOVA, multiple regression and logistic regression tests. Results: The mean and SD of defs index was 8.37 ± 11.2. In the underweight, normal-weight, at risk of overweight and overweight groups, these values were 4.89 ± 10.8, 8.84 ± 11.8, 8.68 ± 10.6, and 10.39 ± 10.2, respectively. Multiple regression analysis revealed a statistically a significant direct association between BMI-for-age and defs index (P = 0.001) after adjusting for gender and age. The percentage of subjects who were caries free and S-ECC was 44.8% and 51.2%, respectively. Logistic regression analysis showed that there was statistically a significant inverse association between BMI-for-age scores and the frequency of caries-free (P = 0.001) and a significant direct association with S-ECC children (P = 0.001). Conclusions : The findings of this study demonstrated that there was an association between higher defs scores and severe early childhood caries with overweightness.